2015
DOI: 10.1002/cpt.89
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study identifies ABCG2 (BCRP) as an allopurinol transporter and a determinant of drug response

Abstract: The first-line treatment of hyperuricemia, which causes gout, is allopurinol. The allopurinol response is highly variable, with many users failing to achieve target serum uric acid (SUA) levels. No genome-wide association study (GWAS) has examined the genetic factors affecting allopurinol effectiveness. Using 2,027 subjects in Kaiser Permanente’s Genetic Epidemiology Research on Adult Health and Aging (GERA) Cohort, we conducted a GWAS of allopurinol-related SUA reduction, first in the largest ethnic group, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(133 citation statements)
references
References 37 publications
5
119
2
7
Order By: Relevance
“…However, two recent studies have highlighted a potential role for ABCG2 in allopurinol response. A significant association between ABCG2 141K and reduced allopurinol response was initially identified in a genome-wide association study 67. However, the definition of response used in this study was allopurinol-related change in serum urate, and there was only assessment of adherence with allopurinol using administrative data.…”
Section: Abcg2 and Allopurinol Responsementioning
confidence: 99%
“…However, two recent studies have highlighted a potential role for ABCG2 in allopurinol response. A significant association between ABCG2 141K and reduced allopurinol response was initially identified in a genome-wide association study 67. However, the definition of response used in this study was allopurinol-related change in serum urate, and there was only assessment of adherence with allopurinol using administrative data.…”
Section: Abcg2 and Allopurinol Responsementioning
confidence: 99%
“…Furthermore, patients homozygous for the reference allele may have lower plasma concentrations of atorvastatin, simvastatin, and fluvastatin [1,87,88] and may respond more poorly to FOLFOX/XELOX therapy [89] compared to patients homozygous for the A allele. Additionally, patients with the AA genotype at c.421 may have reduced response to allopurinol when treated for gout as compared to patients with the AC or CC genotypes [90,91], and a greater incidence of adverse events with gefitinib treatment was reported with the c.421C>A variant [2,38]. The A allele is found more commonly in East Asian populations (27-35% in Japanese and Chinese study participants) than in Caucasian populations (6-14%) and African American populations (1-4%) [4,38,75,92].…”
Section: Abcg2 Variantsmentioning
confidence: 99%
“…These results were further studied in a cohort of 291 Chinese patients to reveal that this altered efficacy was due to an increased bioavailability in these patients [106]. In a recent GWAS in over 1500 multi-ethnic gout patients, the C genotype was associated at genome-wide level significance with worse uric-acid lowering response to allopurinol [90]. One follow up study in 264 patients confirmed this association, even when controlling for adherence to allopurinol, a prevalent factor of non-response in gout treatment [91].…”
Section: Genetic Associationsmentioning
confidence: 99%
“…Differences between these results previously commented may lie on the scarce data on the real impact of ULT on sUA levels, as systematic monitoring of sUA is not available. Genetics may also have an influence on results, as a recent GWAS study [61] has shown the relationship between polymorphisms of the ATP-binding casette, subfamily G, 2 transporter (encoded by the ABCG2 gene) uric acid transporter and the response of sUA to allopurinol [61].…”
Section: Cardiovascular Diseasesmentioning
confidence: 98%